An innovation and entrepreneurship education at the application-oriented universities in China: a conceptual framework - Wang Na; Salmah Topimin; Noor Fzlinda Fabeil; Merlyn Rita Buncha (Asian Scholars Network, 2020)
Innovation and entrepreneurship have been regarded as the main driving forces for China's economic development. Therefore, cultivating innovative and entrepreneurial talent becomes a crucial task and this effort involves educating and training activities which are delivered mainly at universities in China. In transforming and upgrading the Chinese economy, one of the efforts that has been initiated by the government is through the transformation of the colleges and universities in China into the application-oriented universities. The main objectives of the establishment of the application-oriented universities relate to the development of application-oriented education, cultivation of application-oriented talents and construction of application-oriented universities. Through these objectives, it is believed that this new cluster of universities is more relevant in facilitating the economic development and establishing the innovation system of China. However, little is known about the extent to which entrepreneurship education has been implemented in these universities. This paper provides discussion on a relevant literature to support the link between entrepreneurship education and application-oriented universities. A conceptual framework will be developed from the discussion and will be used as a basis for future empirical research.